On a Result of Hardy and Ramanujan - Charsooghi, Mohammad Avalin; Azizi, Yousof; Hassani, Mehdi; Mollazadeh-Beidokhti, Laleh (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce some explicit approximations for the summation $\sum_{k≤ n}Ω(k)$, where $Ω(k)$ is the total number of prime factors of $k$. 2000 Mathematics Subject Classification. 05A10, 11A41, 26D15, 26D20